Pembelajaran Pecahan Melalui Pendekatan PMRI Berbantuan Media Bambu - Khabibatur Rohmah, Dwi Putri; Vika Ivania; Eka Zuliana (Cartesian: Jurnal Pendidikan Matematika, 2024)
This research aims to determine the use of fractional materials using the PMRI approach assisted by bamboo media. The data source in this research was 4th grade students at SD 3 Japan. The method used is a qualitative descriptive research method with descriptive methods. In learning mathematics, fraction material using the PMRI approach using bamboo media is discussing the concept of fractions, determining fraction values, and comparing fraction values. The research results show that after implementing the PMRI learning model students can feel interested, and can expand their mathematical knowledge, and also increase student activity. For example, during the learning process, students dare to interact with each other and between students and teachers.